Pengaruh Strategi Bisnis dan Sistem Pengendalian Manajemen Terhadap Kinerja Keuangan pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Muhammad Irfan Dzul Izzudin; Neneng Dahtiah (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
Natural resource processing industrial companies in the coal mining sub-sector, which are one of the actors of economic activity in the national economy that have an important role in the implementation of the national economy. Several years earlier, some of these companies lost three years in a row which led to the perception that there were irregularities in the company. With a Business Strategy and Management Control System defined appropriately with the condition of the company which is expected to improve the company's financial performance. This study aims to examine how much influence the Business Strategy and Management Control System has on financial performance in the coal mining sub-sector industrial companies. Sources of data in this study are secondary and primary data where the data collection method is through five-year financial reports and through questionnaires distributed to 60 respondents. The data analysis method used in this research is descriptive analysis and simple regression analysis for each independent variable on the dependent variable with the help of the EVIEWS 6 and SPSS version 20 programs. The results of this study indicate that partially business strategy has an effect on Financial Performance with the amount of influence that is 99.04% and the remaining 0.96% is influenced by other variables. Meanwhile, the Management Control System has an effect on Financial Performance with the amount of influence that is 90.4% and 9.6% is influenced by other variables.